Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1161/01.cir.96.7.2302
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III Prevents and Rapidly Reverses Leukocyte Recruitment in Ischemia/Reperfusion

Abstract: This study demonstrates for the first time that thrombin plays an important role in ischemia-induced leukocyte rolling and adhesion and that ATIII can be used therapeutically postreperfusion to attenuate the leukocyte recruitment response in inflammation without the nonspecific effects associated with anti-adhesion molecule therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
2
14

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(152 citation statements)
references
References 42 publications
6
130
2
14
Order By: Relevance
“…Although there was some attenuation of rolling, it was definitely not complete. This is consistent with our previous work showing a role for oxidant-independent mechanisms including thrombin (43). Although O 2 Ϫ can mobilize the stored pool of P-selectin to the endothelial cell surface, where it then mediates leukocyte rolling, this likely occurs via the formation of H 2 O 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Although there was some attenuation of rolling, it was definitely not complete. This is consistent with our previous work showing a role for oxidant-independent mechanisms including thrombin (43). Although O 2 Ϫ can mobilize the stored pool of P-selectin to the endothelial cell surface, where it then mediates leukocyte rolling, this likely occurs via the formation of H 2 O 2 .…”
Section: Discussionsupporting
confidence: 92%
“…[17][18][19] Briefly, umbilical cord veins were rinsed of formed blood products with warm phosphate-buffered saline (PBS), after which the vein was filled with collagenase (320 U/ml in PBS; Worthington Biochemical Corporation, Lakewood, NJ). After a 20-minute incubation period in warm PBS, the cords were gently massaged to ensure detachment of endothelial cells from the vessel wall.…”
Section: Huvec Isolationmentioning
confidence: 99%
“…A flow chamber assay was used as previously described 17 to study leukocyte recruitment from whole blood by cytokine-treated HUVECs (OSM, 1 to 10 ng/ml, or TNF-␣, 25 ng/ml, for 24 hours; thrombin, 0.5 U/ml for 10 minutes). Glass coverslips with confluent monolayers of HUVECs or HDMECs were mounted into a polycarbonate chamber with parallel plate geometry.…”
Section: Flow Chamber Assaymentioning
confidence: 99%
“…Voigt et al 38 demonstrated that ATIII inhibits the binding of the virus to the endothelium. In a recent paper Ostrovsky et al 39 describe that the leukocyte-endothelium interaction was inhibited by ATIII in a feline mesenterial ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%